Condensation of an additive-free cell extract to mimic the conditions of live cells. - Kei Fujiwara (Public Library of Science (PLoS), 2013)
The cellular environment differs from that of reconstituted materials mainly because of the presence of highly condensed biomacromolecules. To mimic the environment and conditions in living cells, we developed a method to prepare additive-free, highly concentrated cell extracts. First, we verified the requirement for specific salts and buffers for functional cell-free translation extracts. The S30 fraction of Escherichia coli cell extracts without additives exhibited sufficient cell-free protein production. Next, we established a method to accumulate biological components by gradual evaporation by using a vacuum desiccator. Bovine serum albumin, green fluorescent protein, alkaline phosphatase, and a diluted reconstituted protein expression system were successfully condensed in their active forms using this method. The protein concentration of the prepared cell extract was elevated to 180 mg/mL, which was expected to contain approximately 260 mg/mL macromolecules, without the loss of cell-free protein expression activity. Such a condensed cell extract may be useful for investigating the differences between cells and reconstituted materials and may contribute to the development of methods to synthesize cells from cell extracts in the future.